Developing a terminology agreement in vocational education research: content validation of standard keyword indexes - Alzet Rama; Nizwardi Jalinus; Muhammad Anwar; Ifdil Ifdil; Wiki Lofandri (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
The study conducted an expert-based content validation to develop and validate a standardized keyword index for vocational education research. A lack of standard terminology in vocational education leads to problems in literature discovery, conducting systematic reviews, and international collaboration. Five content experts (three professors and two doctorate holders) with a minimum of 10 years of experience in vocational education using purposive sampling strategy, evaluated 79 keywords that were extracted from a systematic literature review of recent publications (2014-2025). The experts assessed each keyword for relevance on a 4-point Likert scale. The study used the Content Validity Index (CVI) method for the data analysis at both the item level (I-CVI) and the scale level (S-CVI). The result showed that the content validity was outstanding with the S-CVI/Ave of 0.916 which was higher than the recommended limit of 0.90. The 79 keywords were able to achieve I-CVI scores of at least 0.80, with 46 of the keywords (58.2%) getting perfect agreement (I-CVI = 1.00) and 33 of the keywords (41.8%) I-CVI = 0.80. The validated keywords were categorized into eight thematic categories: Core VET Systems & Models, Pedagogical Approaches, Technical & Occupational Skills, 21st Century & Soft Skills, Industry 4.0 & Emerging Technologies, Policy Standards & Quality Assurance, Labor Market & Economic Development, and Sustainability & Contemporary Issues. This standardized index remedies the problem of terminological inconsistency in vocational education research and thus leads to more efficient literature retrieval, knowledge synthesis, and international research collaboration. The study offers a clear and repeatable framework for keyword standardization that can be used to guide future updates and changes in different educational contexts.